Effects of Peer Support Group on Stress Level among First Semester Nursing Students (Indonesian Journal of Learning Education and Counseling, 2019)
This study aimed to analyze the effects of peer support groups on stress level among first-semester nursing students. This study used a pre-post test quasi-experimental research design with a control group. The samples were 74 nursing students who were assigned to the intervention group and the control group. Data were collected using the instrument of DASS and analyzed using the Wilcoxon test. Results showed that in the intervention group, there was a significant difference in the stress levels before and after the intervention. Meanwhile, in the control group, there was no significant difference in the stress levels before and after the intervention. Peer support groups had a significant effect on reducing stress levels among first-semester nursing students.